2021
DOI: 10.1186/s12874-021-01244-7
|View full text |Cite
|
Sign up to set email alerts
|

Outbreaks of publications about emerging infectious diseases: the case of SARS-CoV-2 and Zika virus

Abstract: Background Outbreaks of infectious diseases generate outbreaks of scientific evidence. In 2016 epidemics of Zika virus emerged, and in 2020, a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) caused a pandemic of coronavirus disease 2019 (COVID-19). We compared patterns of scientific publications for the two infections to analyse the evolution of the evidence. Methods We annotated publications on Zika virus and SARS-CoV-2 that we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
(20 reference statements)
0
14
0
Order By: Relevance
“…This covers the period when vaccines started to be rolled out and the alpha variant of concern became dominant in high-income countries. Although we made extensive efforts to comply with the planned 3 monthly updates, with weekly searches and a continuous process of screening, data extraction and risk of bias assessment, the pace of publications about SARS-CoV-2 exceeds the capacity of our crowd of reviewers [ 10 , 26 ]. Our decision to include preprints compensates for some of the delay because these articles appear sooner than peer-reviewed publications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This covers the period when vaccines started to be rolled out and the alpha variant of concern became dominant in high-income countries. Although we made extensive efforts to comply with the planned 3 monthly updates, with weekly searches and a continuous process of screening, data extraction and risk of bias assessment, the pace of publications about SARS-CoV-2 exceeds the capacity of our crowd of reviewers [ 10 , 26 ]. Our decision to include preprints compensates for some of the delay because these articles appear sooner than peer-reviewed publications.…”
Section: Discussionmentioning
confidence: 99%
“…Since late 2020, vaccines have become available [ 8 ] and several SARS-CoV-2 variants of concern have spread internationally, with varying viral characteristics [ 9 ]. The number of published studies about SARS-CoV-2 is increasing continuously, and the types of published studies are also changing [ 10 ], including the designs of studies about asymptomatic infection. In systematic reviews of studies published to April 2021, reported point estimates from random effects meta-analysis models range from 17% to 41% [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of the methods for this living systematic review is that this update only includes published studies up to 2 February 2021. Although we made extensive efforts to comply with the planned 3-monthly updates, with weekly searches and a continuous process of screening, data extraction and risk of bias assessment, the pace of publications about SARS-CoV-2 exceeds the capacity of our crowd of reviewers [8, 20]. In reviews of observational epidemiological studies, search terms are broad so the number of studies that needs to be screened is high, but the yield of included studies is low.…”
Section: Discussionmentioning
confidence: 99%
“…Since late 2020, vaccines have become available [8] and several SARS-CoV-2 variants of concern have spread internationally, with varying viral characteristics [9]. The number of published studies about SARS-CoV-2 is also increasing continuously and the types of published studies are also changing [10], including the designs of studies about asymptomatic infection. In systematic reviews of studies published to April 2021, reported point estimates from random effects meta-analysis models range from 17 to 41% [11][12][13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation